<em>The question has inconsistent or incomplete data, so I'm filling the holes with key data.</em>
Answer:
<em>Every people at dinner received one-tenth of the original turkey= 0.1</em>
Step-by-step explanation:
<u>Proportions</u>
If some fraction a/b of a whole total M is to be computed and later removed, we proceed as follows
* Compute the portion to be removed as a/b*M
* Subtract it from the total quantity: M-a/b*M=M(1-a/b)
I'm assuming 1/5 of the turkey was lost due to overcooking. It means that (1-1/5) of the turkey remained for dinner, that is, 4/5 of the turkey.
Each people at dinner received the same amount of the remaining, so we must divide 4/5 by 8, to get 4/40, or 1/10. It means that every people at dinner received one-tenth of the original turkey
Answer: choice B
Explanation: Go through each answer choice and try the Pythagorean theorem to see if it works. This is because a right triangle’s side lengths are described by the Pythagorean theorem. one side^2 + second side^2 = longest side^2. In a right triangle, this equation will be true. Let me show you what I mean
For answer choice A:
(root 2)^2 + (root 3)^2 = (root 4)^2
2 + 3 = 4
5 = 4
5 does not equal 4. Therefore it cannot be A.
For answer choice B:
(root 8)^2 + (3)^2 = (root 17)^2
8 + 9 = 17
17 = 17
this is true! therefore this is a right triangle and it’s B
Answer:
I'm not sure what all that extra stuff is supposed to mean, but the answer to the top question is: x = -6
Step-by-step explanation:
Answer:
first, you need to get y on one side. So, because the x is negative it becomes positive when you switch it to the other side. 3y= 9x+5. You then need to divide all parts by 3. 3/3= 1 so thats just y. 9/3 is 3 so thats 3x. then 5/3 is a fraction that you can write as just 5/3 or 1 and 2/3. That would leave you with y= 3x + 5/3. Then x (3) is your slope. and what you add to it (5/3) is your y int.
Answer:
y = (5/4)2^x
Step-by-step explanation:
The function value increases by a factor of 40/10 = 4 when x increases by 2. The function can be written as ...
y = (reference value)·(growth factor)^((x -reference)/(change in x for growth factor))
y = 10·4^((x-3)/2) . . . . . . using point (3, 10) as a reference
This can be simplified to ...
y = 10·2^(x -3) = 10/8·2^x
y = (5/4)2^x